KARAKTERISTIK DAN GENESA TUFA ZEOLITIK DI DAERAH BANTENGWARENG, KECAMATAN GEDANGSARI, KABUPATEN GUNUNGKIDUL, PROPINSI DAERAH ISTIMEWA YOGYAKARTA - , Selvi Yuminti, Widiasmoro, Anastasia Dewi Titisari ([Yogyakarta] : HAGI-IAGI-PERHAPI, 2005)
The natural zeolite constitute hydrate sillicate alluminous compound which physical and chemically capable as absorbent and cation exchange. Because of its benefit, then research about characteristic and the genesis of zeolitic tuff has been done. Gunungkidul area is one of zeolite occurrence in Daerah Istimewa Yogyakarta. It's zeolitic tuff part of Kebo-Butak Formation. Type of zeolite are mordenite and linoptilolite, in association of montmorilonite, which are genetically interpreted as a product of volcanic glass alteration. Other minerals are feldspar and quartz, as well as volcanic glass. The physical character of the zeolitic tuff are hardness about 2,5 &ndash